Primary Esophageal Motility Disorders: Beyond Achalasia - Schlottmann, Francisco (Int J Mol Sci, 2017)
The best-defined primary esophageal motor disorder is achalasia. However, symptoms such as dysphagia, regurgitation and chest pain can be caused by other esophageal motility disorders. The Chicago classification introduced new manometric parameters and better defined esophageal motility disorders. Motility disorders beyond achalasia with the current classification are: esophagogastric junction outflow obstruction, major disorders of peristalsis (distal esophageal spasm, hypercontractile esophagus, absent contractility) and minor disorders of peristalsis (ineffective esophageal motility, fragmented peristalsis). The aim of this study was to review the current diagnosis and management of esophageal motility disorders other than achalasia.